2008
DOI: 10.1016/j.pain.2007.08.038
|View full text |Cite
|
Sign up to set email alerts
|

A typology of pain coping strategies in pediatric patients with chronic abdominal pain

Abstract: This study aimed to identify clinically meaningful profiles of pain coping strategies used by youth with chronic abdominal pain (CAP). Participants (n = 699) were pediatric patients (ages 8-18 years) and their parents. Patients completed the Pain Response Inventory (PRI) and measures of somatic and depressive symptoms, disability, pain severity and pain efficacy, and perceived competence. Parents rated their children's pain severity and coping efficacy. Hierarchical cluster analysis based on the 13 PRI subscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 35 publications
7
83
2
2
Order By: Relevance
“…Walker et al [14] identified six coping profiles in examining coping with pain by using cluster analysis: 'infrequent', 'self-reliant', 'engaged', 'inconsistent', 'avoidant', and 'dependent'. 'Infrequent' copers rarely used any of the pain-coping strategies.…”
Section: Coping Profiles In Previous Person-oriented Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Walker et al [14] identified six coping profiles in examining coping with pain by using cluster analysis: 'infrequent', 'self-reliant', 'engaged', 'inconsistent', 'avoidant', and 'dependent'. 'Infrequent' copers rarely used any of the pain-coping strategies.…”
Section: Coping Profiles In Previous Person-oriented Studiesmentioning
confidence: 99%
“…'Low generic high integrated' copers used high levels of diabetes integration and low levels of all other coping strategies. Only one common coping profile was identified in both these studies: the group of 'passive/avoidant' copers [9,14].…”
Section: Coping Profiles In Previous Person-oriented Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28][29][30][31][32] Further, barriers to assessment stem from a lack of awareness among health professionals of psychometrically sound tools and/or a lack of standardization within organizations for routine chronic pain assessment. [32][33][34] Although previous reviews have identified measures to inform clinical practice, the application to children with disabilities is lacking. [27][28][29][30][31]35,36 Therefore, the primary aim of this review was to identify, describe, and critique pediatric chronic pain assessment tools currently available and make recommendations for clinical use for children with CP.…”
mentioning
confidence: 99%